2021
DOI: 10.1002/jca.21960
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of comatose patient from cyclobenzaprine overdose with therapeutic plasma exchange

Abstract: We present a case of a 15‐year‐old female who was admitted in a comatose state with no spontaneous respiratory effort and absence of brainstem reflexes after cyclobenzaprine ingestion. Due to severe presentation and recent ingestion of high plasma protein binding medication with long half‐life, therapeutic plasma exchange (TPE) was performed and resulted in full neurological recovery. This case explores the role of TPE as an effective treatment option for life‐threatening cyclobenzaprine overdose. TPE is gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Hucker et al ( 1 ) showed that peak plasma levels in dogs are reached after 2 h when given a 2 mg/kg dose orally or intravenously. Cyclobenzaprine is 93% protein-bound ( 9 , 11 , 17 ), is widely distributed to the tissues ( 14 , 17 ), and undergoes enterohepatic recirculation ( 12 14 ). It is extensively metabolized in the liver by cytochrome P450, 1A2, and 3A4 ( 9 , 11 , 13 – 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hucker et al ( 1 ) showed that peak plasma levels in dogs are reached after 2 h when given a 2 mg/kg dose orally or intravenously. Cyclobenzaprine is 93% protein-bound ( 9 , 11 , 17 ), is widely distributed to the tissues ( 14 , 17 ), and undergoes enterohepatic recirculation ( 12 14 ). It is extensively metabolized in the liver by cytochrome P450, 1A2, and 3A4 ( 9 , 11 , 13 – 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…While some metabolites are excreted in the feces ( 1 ), the majority are excreted via the kidneys as a glucuronide ( 1 , 9 , 13 , 14 ). The elimination half-life is approximately 18 h but can range between 8 and 37 h ( 13 , 14 , 17 ). The LD50 is 338 and 425 mg/kg in mice and rats, respectively ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation